2010
DOI: 10.1016/j.canep.2010.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 G870A polymorphism is associated with an increased risk of hepatocellular carcinoma in the Turkish population: Case–control study

Abstract: Our results suggest that the CCND1 G870A single nucleotide polymorphism is associated with an increased risk of HCC in our Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 32 publications
3
36
0
1
Order By: Relevance
“…In the study by Pakakasama et al (2004), which described the association between the G870A SNP and hepatocellular carcinoma risk in 3 races, the distribution of the G870A genotypes in controls of Hispanics were not in accordance with HWE and this study was therefore excluded from the meta-analysis. The study by Pakakasama et al (2004) examining African Americans and Caucasians and 3 other studies (Zhang et al, 2002;Akkiz et al, 2010;Hu et al, 2014), containing 540 cases and 626 controls, were included in the meta-analysis to determine the role of the G870A polymorphism on hepatocellular carcinoma risk. Figure 2 shows the main results of this meta-analysis regarding the association between the CCND1 G870A polymorphism and the susceptibility to leukemia.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Pakakasama et al (2004), which described the association between the G870A SNP and hepatocellular carcinoma risk in 3 races, the distribution of the G870A genotypes in controls of Hispanics were not in accordance with HWE and this study was therefore excluded from the meta-analysis. The study by Pakakasama et al (2004) examining African Americans and Caucasians and 3 other studies (Zhang et al, 2002;Akkiz et al, 2010;Hu et al, 2014), containing 540 cases and 626 controls, were included in the meta-analysis to determine the role of the G870A polymorphism on hepatocellular carcinoma risk. Figure 2 shows the main results of this meta-analysis regarding the association between the CCND1 G870A polymorphism and the susceptibility to leukemia.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The relationships between the G870A SNP and excessive CCND1 activity, as well as numerous human tumors, have been studied in recent years, including primary brain tumors, bladder cancer, colorectal cancer, esophageal cancer, hepatocellular carcinoma, leukemia, and breast cancer (Akkiz et al, 2010;Zhuo et al, 2012;Bedewy et al, 2013;Sameer et al, 2013;Zeybek et al, 2013;Li et al, 2014). Among these, the numerous relevant epidemiologic studies investigating the relationship between the CCND1 G870A variant and hepatocellular carcinoma (Zhang et al, 2002;Pakakasama et al, 2004;Akkiz et al, 2010;Hu et al, 2014) or leukemia (Howe and Lynas, 2001;Hou et al, 2005;Bedewy et al 2013) have yielded conflicting and controversial results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified a correlation between the CCND1 870A allele and an increased cancer risk, including bladder , prostate ,liver and breast cancer (Wang et al, 2002;Wang et al, 2003;Akkiz et al, 2010;Canbay et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicate that the CCND1 gene has a G to A polymorphism, and the CCND1 870A allele expresses transcript B (cyclin D1b), which affects the risk of malignant tumors (Betticher et al, 1995;Bala et al, 2001;Qiuling et al, 2003;Wang et al, 2003). CCND1 gene has been reported in various tumors (Akkiz et al, 2010;Yang et al, 2012;Wang et al, 2014). Similarly, the CCND1 G870A gene polymorphism also has been reported in various tumors in Asian Pacific journal of cancer prevention (APJCP) during the last two years, but the results of previous studies were inconsistent (Li et al, 2012;Zeybek et al, 2013).…”
mentioning
confidence: 99%